Interpersonal relationships in Hungary – an overview - Albert, Fruzsina; Dávid, Beáta (METSZETEK Társadalomtudományi Folyóirat, 2018)
Our paper aims to demonstrate that social structure has significant impact on the formation of interpersonal relations. We review and analyse the characteristics of ego-centric interpersonal networks of Hungarians based on data from nationally representative adult population surveys between the mid-1980’s up to 2015. We focus especially on core discussion networks, friendship ties and weak ties and analyse how the transition to market economy influenced interpersonal relationships. As expected, the large-scale social changes brought about by the transition changed interpersonal networks as well. During the first decade of the transition (in the 1990’s) one could not witness a significant change of personal networks, nonetheless the adaptation process was easier for people supported by strong, traditional family ties. Non-kin ties, especially friendships seem to gain significance at the expense of kin relationships. Overall, resources available through weak ties seem to be decreasing.